Evaluation of anxiety, depression, and quality of life in patients with acne vulgaris, and quality of life in their families - Hatice Duman; Ilteris Oguz Topal; Emek Kocaturk; Mehmet Ali Duman (Dermatologica Sinica, 2016)
Background/Objectives: Dermatological diseases not only affect patients' lives but also the lives of their family members. Our aim was to evaluate anxiety and depression risk in patients with acne vulgaris and the effect of acne vulgaris on quality of life of the patients and their families. Methods: A total of 125 patients with acne vulgaris, 110 of their family members, and 100 healthy volunteers were included in the study. Patients with acne vulgaris were requested to complete the Acne Quality of Life Scale (AQOL) and Hospital Anxiety and Depression Scale (HAD) at the time of the first admission and 2 months later. The healthy volunteers were only asked to complete the HAD, and the family members filled out the Family Dermatology Life Quality Index (FDLQI) at the time of the first admission and 2 months later. Results: The acne and control groups showed no significant differences between the HAD anxiety subscale (HAD-A) and HAD depression subscale (HAD-D) scores. The mean AQOL score of the patients was 6.8 ± 5.3. AQOL scores were positively correlated with HAD-A, HAD-D and FDLQI scores. The mean score of the FDLQI was 7.6 ± 5.3. FDLQI scores showed a statistically significant change after 2 months (p = 0.001). Conclusion: Acne vulgaris does not have an effect on quality of life and the risk of anxiety or depression. In the cases of acne, when the quality of life decreases, the risk of depression as well as anxiety increases and the quality of life of the family members is negatively affected. Acne vulgaris negatively affects the quality of life of the family members of the patients.